Lightweight heat and sound insulation material and its manufacturing method
The integration of silica aerogel particles and organic nanofibers within a nonwoven fabric or open-cell foam creates a lightweight, effective sound insulation material that addresses the limitations of existing technologies in both low and high-frequency sound management.
Patent Information
- Application Number
- JP2020146463
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-01
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2040-09-01
AI Technical Summary
Existing sound insulation materials are either heavy and inefficient at low-frequency sound insulation or lightweight but lacking in effective sound absorption and insulation properties.
A heat-insulating sound insulation material is created by impregnating a nonwoven fabric or open-cell foam with an aqueous dispersion containing silica aerogel particles and organic nanofibers with anionic functional groups, forming a solid composite with a three-dimensional continuous structure.
The material achieves excellent sound insulation across low and high frequencies, is lightweight, and reduces powder fall-out, while maintaining high porosity and thermal insulation properties.
Smart Images

Figure 0007671131000004 
Figure 0007671131000005 
Figure 0007671131000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat and sound insulating material which is lightweight and has excellent heat and sound insulating properties, and a method for producing the same. [Background technology]
[0002] There is a demand for noise control measures to improve comfort in automobiles, railway vehicles, and aircraft, and lightweight materials are also required from the viewpoint of energy conservation. Sponge-like foams such as urethane foam, glass wool, and nonwoven microfiber fabrics are used as sound-absorbing materials, while rubber-like sheets such as butyl rubber are used as sound-proofing materials. Sound-absorbing materials made from foam or nonwoven fabric have excellent sound-absorbing properties because their continuous pores reduce the pressure of air vibrations caused by sound. However, it is difficult to completely block air vibrations, and air vibrations pass through the material, making it difficult to achieve sufficient sound insulation. Rubber-like soundproofing sheets have high soundproofing properties by blocking air and preventing the transmission of vibrations, but they have problems in that they are prone to sound reflection and are heavy.
[0003] As a sound insulation material, a sound insulation material is known which is made by adding a filler having a relatively large specific gravity to natural rubber, synthetic rubber such as styrene-butadiene rubber, polybutadiene rubber, polyisoprene rubber, and chloroprene rubber, resin such as PVC (polyvinyl chloride) and EVA (ethylene-vinyl acetate copolymer), bitumen, etc., kneading the mixture, and processing the mixture into a sheet shape using a processing machine such as a calendar roll. Such sound insulation materials are trimmed to a required shape or three-dimensionally molded, and are directly attached to a location where sound insulation is required, or are laminated with a fiber-based sound absorption material or a resin foam-based sound absorption material, or are molded into a required shape to be used as a sound absorbing and insulating material. Applications are wide, and include a wide range of applications such as automobiles and other transportation machines, various home appliances, and building materials. However, such sound insulation materials follow the mass law, and require a large weight to achieve sound insulation, and have a problem of low sound insulation at low frequencies.
[0004] Lightweight heat and sound insulation materials using silica aerogel have been proposed. Patent Document 1 describes a method for producing a high-strength, lightweight silica aerogel molded body, which contains an alkaline water glass, a water glass hardener, a water-soluble organic polymer, and water, and in the solution before gelation, the mixture has a multi-phase structure consisting of a sea phase and an island phase, and a solidified gel reflecting the multi-phase structure is generated, taken out, and the water in the gel and, if necessary, further water-soluble organic components are burned and removed. According to this, it is necessary to perform baking at a high temperature of 800°C for 2 to 3 hours to remove the contained organic matter, which is not preferable from the viewpoint of energy saving.
[0005] Patent Document 2 describes a thermal insulation material that can be obtained from a mixture of an aqueous foam, silica aerogel particles, and an organic binder and / or an inorganic binder. The cationic surfactant salt and anionic surfactant salt that form the aqueous foam do not evaporate at the drying temperature and remain, and it is considered that they enter the pores of the silica aerogel, preventing the inherent performance of the silica aerogel from being utilized.
[0006] Patent Document 3 describes an insulating composite material containing inorganic aerogel and melamine foam. A method is adopted in which an open-cell foam is impregnated with a sol solution to form a wet gel, and then the gel is dried, and melamine foam is used as the open-cell foam. However, as in the case of nonwoven fabric, melamine foam cannot prevent the aerogel from falling off, and the loss of aerogel reduces the insulating performance.
[0007] Patent Document 4 describes a strong solid composite with excellent heat insulation and sound absorption properties, which is formed by drying an aqueous dispersion of silica aerogel particles obtained by dispersing silica aerogel particles in a dispersion medium containing organic nanofibers having an anionic functional group, a water-soluble nonionic surfactant, and water. When producing a thick sheet, there is a problem that it must be formed by laminating thin sheets because cracks occur during drying. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 11-139819 [Patent Document 2] Special Publication No. 2013-518961 [Patent Document 3] Special Publication No. 2016-521670 [Patent Document 4] JP 2018-43927 A Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a heat insulating sound insulating material which is lightweight, has little powder falling off, and has excellent heat insulating and sound insulating properties, and to provide a method for producing the heat insulating sound insulating material which is simple, energy saving, and has little environmental impact. [Means for solving the problem]
[0010] As a result of intensive research into achieving the above-mentioned object, the inventors have completed the present invention, which relates to a thermal and sound insulating material obtained by impregnating a nonwoven fabric or an open-cell foam with an aqueous dispersion containing organic nanofibers and silica aerogel particles, which is obtained by adding silica aerogel particles to an aqueous solution containing organic nanofibers having an anionic functional group and a water-soluble nonionic surfactant, and then drying the aqueous dispersion.
[0011] The present invention is characterized by having the following configuration and is intended to solve the above problems. [1] A thermal and acoustic insulation material whose basic structure is cells in which aggregates of silica aerogel particles are surrounded by a network of organic nanofibers with anionic functional groups. A solid composite with a three-dimensional continuous structure in which multiple cells are closely spaced is formed inside a nonwoven fabric or open-cell foam. [2] The heat insulating and sound insulating material according to [1], characterized in that the nonwoven fabric is made of at least one of natural fibers, inorganic fibers, regenerated fibers, semi-synthetic fibers, and synthetic fibers. [3] The heat insulating and sound insulating material according to [1], characterized in that the open-cell foam is at least one type of open-cell foam selected from the group consisting of urethane resin, melamine resin, vinyl acetate resin, polyvinyl chloride resin, acrylic resin, epoxy resin, silicone resin, olefin resin, latex, and rubber. [4] The sound-proofing material according to [1], wherein the nonwoven fabric is glass wool or rock wool. [5] The heat insulating soundproofing material according to [4], characterized in that the normal incidence sound transmission loss in the frequency band of 200 Hz to 2000 Hz is 20 dB or more. [6] A method for producing a thermal and sound insulating material, comprising the steps of: adding silica aerogel particles to an aqueous solution containing organic nanofibers having an anionic functional group and a water-soluble nonionic surfactant; and impregnating a nonwoven fabric or an open-cell foam with an aqueous dispersion containing the organic nanofibers and silica aerogel particles; and drying the aqueous dispersion.
[0012] The nonwoven fabric generally refers to a material in which fibers are intertwined without being woven. However, in the present invention, even a cloth or woven material in which fibers are combined lengthwise and widthwise can be used as long as the gaps between the fibers can be impregnated with an aqueous dispersion of silica aerogel particles.
[0013] The open-cell foam is a foam having a structure in which the cells are connected to each other like a sponge, and can absorb water and allow gas to pass through.
[0014] The normal incidence sound transmission loss is a sound insulation performance value calculated by the following formula for the energy of incident sound (Ii) that is perpendicularly incident on a sample and the energy of transmitted sound (It), and the larger the value, the better the sound insulation. Sound transmission loss (TL)=10log 10 (Ii / It) In the present invention, this is a value obtained by measuring the normal incidence sound transmission of an acoustic material based on the transfer matrix method in accordance with ASTM-E2611. Effect of the Invention
[0015] A thermal insulation and soundproofing material obtained by impregnating a nonwoven fabric or an open-cell foam with an aqueous dispersion containing organic nanofibers and silica aerogel particles and then drying the material is lightweight, has little powder falling off, and has excellent thermal insulation and soundproofing properties, or soundproofing properties in both low and high frequency ranges.
[0016] In the thermal insulation soundproofing material of the present invention, the solid composite is present inside the nonwoven fabric or open-cell foam, and in the solid composite, aggregates of silica aerogel particles are surrounded by a net of organic nanofibers, so that there is almost no powder falling off of the silica aerogel particles.
[0017] The heat insulating sound insulating material of the present invention maintains its low density and the nanopores of silica aerogel, making it suitable as a sound insulating material, and is lightweight and has excellent sound insulating properties or sound insulating properties in the low and high frequency ranges.
[0018] The heat insulating sound insulation material of the present invention blocks low-frequency sounds of 250 Hz or less, and can effectively insulate road noise, such as the low-pitched "roaring" sound that is generated by transportation equipment such as automobiles, ships, airplanes, and helicopters, factory blowers, presses, vacuum pumps, outdoor air conditioner units of stores and public facilities, boilers, etc.
[0019] When impregnated into glass wool or rock wool, the thermal insulating soundproofing material of the present invention has excellent soundproofing properties over the entire frequency range below 2000 Hz, and can effectively insulate not only the unpleasant low-frequency sounds mentioned above, but also the "whissing" pattern noise that occurs when a car is running at around 1000 Hz.
[0020] The thermal insulation sound-proofing material of the present invention, when using a nonwoven fabric or an open-cell foam other than glass wool or rock wool, exhibits sound-proofing performance having excellent sound-proofing properties in the low and high frequency ranges and frequency selectivity for transmitting mid-frequency sounds, thereby reducing the above-mentioned unpleasant low-frequency sounds and unpleasant high-frequency sounds that humans are most sensitive to and hear, such as the squealing sounds that occur when scratching glass or metal, and selectively allowing the sounds of everyday conversation, pleasant sounds in the range of the main melody of music, sirens, etc., to transmit. [Brief description of the drawings]
[0021] [Figure 1] Normal incidence transmission loss for frequency of the heat insulating sound insulation material of Example 1 and Comparative Example 1 [Diagram 2] Normal incidence transmission loss for frequency of the heat insulating sound insulation material of Example 1, Comparative Example 2, Calculation Example 1, and Calculation Example 2 [Diagram 3] Normal incidence transmission loss versus frequency for the heat insulating sound insulation materials of Examples 1 and 2 [Figure 4] Normal incidence transmission loss versus frequency for the heat insulating sound insulation materials of Examples 3, 4, 5, and 6 [Diagram 5] Optical microscope photograph of the heat and sound insulation material of Example 1 [Figure 6] Schematic of solid composite [Figure 7] Schematic diagram of heat and sound insulation material formed on nonwoven fabric DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The thermal insulation and soundproofing material of the present invention is a composite material in which a solid composite having a three-dimensional continuous structure in which a plurality of cells are closely spaced from each other is formed inside a nonwoven fabric or an open-cell foam, and which is basically composed of cells in which aggregates of silica aerogel particles are surrounded by a network of organic nanofibers having anionic functional groups. The composite material is lightweight, has high soundproofing properties, and is almost free of powder falling off.
[0023] The nonwoven fabric constituting the heat insulating sound insulation material of the present invention is not particularly limited, but includes natural fibers (plant fibers such as cotton fibers and hemp fibers, and animal fibers such as silk and wool), inorganic fibers (glass fibers, artificial mineral fibers, carbon fibers), regenerated cellulose fibers (viscose, rayon, polynosic, cupra, lyocell), semi-synthetic fibers (acetate, triacetate, promix), and synthetic fibers (polyaramid fibers such as nylon and aramid, polyester, acrylic, vinylon, vinylidene, polyvinyl chloride, polyurethane, polyarylate, polyethylene, polypropylene, polychlar, and polylactic acid). Hydrophilic nonwoven fabrics are preferred because the aqueous dispersion is easily permeated into the interior. From the viewpoint of heat resistance, inorganic fibers, aramid fibers, plant fibers, regenerated cellulose fibers, semi-synthetic fibers, polyester fibers, polyarylate fibers, and vinylon fibers are more preferred. More preferred are inorganic fibers such as glass fibers (glass wool), artificial mineral fibers (rock wool), and carbon fibers, and aramid fibers. Furthermore, in the present invention, not only nonwoven fabrics but also cloth or woven fabrics made of a combination of fibers can be used as long as the gaps between the fibers can be impregnated with an aqueous dispersion of silica aerogel particles.
[0024] The open-cell foam constituting the heat insulating sound insulation material of the present invention is not particularly limited, but examples thereof include open-cell foams of urethane resin, melamine resin, vinyl acetate resin, vinyl chloride resin, acrylic resin, epoxy resin, silicone resin, olefin resin, latex, and rubber. Hydrophilic open-cell foams are preferred because the aqueous dispersion of silica aerogel particles can easily penetrate into the interior. The open-cell foam is a foam of the above material that contains air bubbles inside and the air bubbles are connected to each other like a sponge, and has a structure that can absorb water and pass gas.
[0025] Next, the solid composite is obtained by drying an aqueous dispersion containing organic nanofibers and silica aerogel particles, the aqueous dispersion being obtained by dispersing silica aerogel particles in a dispersion medium containing organic nanofibers having an anionic functional group, a water-soluble nonionic surfactant, and water.
[0026] The solid composite obtained by drying the aqueous dispersion is a solid composite having a three-dimensional continuous structure in which a plurality of cells are closely spaced, with the basic structure being composed of cells in which aggregates of silica aerogel particles are surrounded by a network of organic nanofibers having anionic functional groups. A schematic diagram of the solid composite is shown in Figure 6. Optical microscope photographs of the solid composite made of silica aerogel and cellulose nanofibers are shown in Figures 2, 4, and 5 of the Examples of Patent Document 4.
[0027] The thermal and acoustic insulation material of the present invention is a composite material obtained by impregnating a nonwoven fabric or an open-cell foam with the mixed aqueous dispersion and drying the mixture to form the solid composite in the internal space of the nonwoven fabric or the open-cell foam.
[0028] The organic nanofibers having an anionic functional group are not particularly limited, and examples thereof include organic nanofibers having an anionic functional group such as a carboxyl group and a salt of a carboxyl group, a phosphoric acid group and a salt of a phosphoric acid group, a sulfate ester group and a salt of a sulfate ester group, etc. Furthermore, the salts of the carboxyl group, the salts of the phosphoric acid group, and the salts of the sulfate ester group may be alkali metal salts, alkaline earth metal salts, ammonium salts, etc.
[0029] Particularly preferred anionic functional groups are salts of the sulfate group or sulfate ester group, and examples of the salts of the sulfate ester group include sodium salt, calcium salt, potassium salt, and ammonium salt of sulfated cellulose nanofiber, and salts of at least one sulfate ester group of a tetraalkylammonium base.
[0030] Examples of organic nanofibers having anionic functional groups include natural polysaccharide nanofibers such as cellulose nanofibers, chitin nanofibers, and chitosan nanofibers that have been modified or denatured to have anionic functional groups on their surface, and organic nanofibers obtained by natural formation or artificial processing from polymers having carboxyl groups such as agar, gelatin, hyaluronic acid, CMC, and polyacrylic acid. Of these, natural polysaccharide nanofibers such as cellulose nanofibers, chitin nanofibers, and chitosan nanofibers that have been modified or denatured to have anionic functional groups on their surface are more preferred because they have a high degree of crystallinity, thixotropy, and viscosity.
[0031] The degree of crystallinity of the organic nanofibers having anionic functional groups is preferably 30% or more, more preferably 40% or more. Organic nanofibers with a high degree of crystallinity have high thixotropy and viscosity, and can stabilize the micelles into which the aerogel particles are incorporated, and the dried composite is strong and has excellent water resistance, which is preferable. The most preferred organic nanofibers having anionic functional groups are cellulose nanofibers and chitin nanofibers that have been modified or denatured to have anionic functional groups on their surfaces.
[0032] Specific examples of particularly preferred organic nanofibers having an anionic functional group include organic nanofibers having the above-mentioned carboxyl group or a salt of a carboxyl group as the anionic functional group, such as TEMPO-oxidized cellulose nanofibers and carboxymethyl-modified cellulose nanofibers.
[0033] In addition, the greater the degree of substitution of the anionic functional group on the surface of the organic nanofiber, the higher the hydration of the organic nanofiber, and therefore the greater the effect of improving the viscosity and thixotropy of the dispersion medium. Therefore, the average degree of substitution of the anionic functional group on the surface of the organic nanofiber is preferably 0.10 to 1.00, more preferably 0.15 to 0.95, and even more preferably 0.20 to 0.90. If it is 0.1 or less, the thickening effect and the interaction with the nonionic ether surfactant are reduced. On the other hand, if it is 1.0 or more, the crystallinity of the nanofiber decreases, the thixotropy decreases, and the fiber shape collapses, which may result in a decrease in the thickening effect and a decrease in the strength of the composite material after drying.
[0034] The average fiber diameter of the organic nanofibers having an anionic functional group is preferably 2 to 500 nm, more preferably 5 to 300 nm, and further preferably 10 to 200 nm. If it is 2 nm or less, the manufacturing cost of the nanofiber increases and the heat resistance decreases. In addition, the crystallinity may decrease. On the other hand, if it is 500 nm or more, the surface area decreases and the thixotropy may be lost. Furthermore, if the fiber diameter is large, the surface area decreases and it becomes impossible to incorporate and fix the silica aerogel particles in the nanofiber network, so that the composite material after drying may become brittle or dust may be generated due to the falling off of the silica aerogel particles.
[0035] Furthermore, the average fiber length of the organic nanofibers is preferably 0.2 to 50 μm, more preferably 0.3 to 35 μm, even more preferably 0.5 to 30 μm, and most preferably 1.0 to 20 μm. If the fiber length is too small, the network will be weak.
[0036] The dispersion medium for dispersing the silica aerogel particles to obtain the solid composite of the heat insulating and sound insulating material of the present invention contains organic nanofibers having an anionic functional group, a water-soluble nonionic surfactant, and water. The water-soluble nonionic surfactant includes hydrophilic nonionic surfactants that dissolve in water when used as a dispersion medium, even if they have low solubility and are not completely miscible with water.
[0037] The water-soluble nonionic surfactant is not particularly limited, and examples of water-soluble ether surfactants such as ethylene glycol or polyethylene glycol alkyl ether, propylene or polypropylene glycol alkyl ether, glycerin or polyglycerin ether, alkyl glycoside, etc., and water-soluble ester surfactants such as sucrose fatty acid ester, polyglycerin fatty acid ester, etc. Among these, ether-type nonionic surfactants represented by the following formula (1) or (2), which are nonionic ether-type surfactants with excellent water solubility, are preferred. R1-O-(CH2-CH2-O) n -R2 (1) R1-O-(CH 2- CH 2- CH 2- O) n -R2 (2) (In formula (1) and formula (2), R1 is a hydrogen atom, an alkyl group having 10 or less carbon atoms, a cycloalkyl group having 5 to 10 carbon atoms, or an alkenyl group having 10 or less carbon atoms; R2 is an alkyl group having 3 to 10 carbon atoms, a cycloalkyl group having 5 to 10 carbon atoms, or an alkenyl group having 10 or less carbon atoms; and n is 1 to 20.)
[0038] Furthermore, the water-soluble nonionic surfactant is preferably at least one amphiphilic alcohol having 4 to 7 carbon atoms and represented by the following formula (3). HO-R3 (3) (In formula (3), R3 is an alkyl group having 4 to 7 carbon atoms.) Methanol, ethanol, 2-propanol, or isobutyl alcohol, which are highly polar and have 3 or less carbon atoms, are weak surfactants and do not mix well with hydrophobic silica aerogel, so even if a small amount (e.g., 15% or less) is added, the hydrophobic silica aerogel cannot be dispersed, and if a large amount (e.g., 15% or more) is added, the dispersion medium penetrates into the pores of the silica aerogel, causing the silica aerogel to shrink violently after drying, which is not preferable. Alcohols with 8 or more carbon atoms are not preferable because they are poorly soluble in water or cannot be dissolved, making it difficult to obtain a uniform silica aerogel dispersion.
[0039] It is particularly preferable to use a water-soluble nonionic ether surfactant represented by formula (1) or (2) or an amphiphilic alcohol represented by formula (3) so that the hydrophobic silica aerogel particles are dispersed in the dispersion medium as aggregates. After drying such a dispersion, the silica aerogel particles are incorporated into the network of the organic nanofibers having anionic functional groups while remaining as aggregates, and therefore the content of the organic nanofibers is low, so that the silica aerogel does not shrink or fall off, resulting in a composite that is strong and has excellent sound insulation properties. Furthermore, the water-soluble nonionic ether type surfactant and / or the amphiphilic alcohol having 4 or more carbon atoms can be used in combination with an ester type hydrophobic nonionic surfactant.
[0040] Considering that the dispersion will be dried to produce a composite material, a surfactant with a boiling point of 300° C. or less is preferable. If the boiling point of the surfactant is too high, it will be difficult to evaporate, and when the dispersion is dried and molded into a composite material, the surfactant will remain in the composite, which may reduce the heat resistance of the composite, which is not preferable.
[0041] Among the ether-type nonionic surfactants represented by the above formulas (1) and (2), ether-type nonionic surfactants having a small number of carbon atoms in R1 and R2, a small n, and a boiling point of 300° C. or less are preferred.
[0042] Examples of ether-type nonionic surfactants having a boiling point of 300° C. or less include at least one selected from the group consisting of ethylene glycol monoalkyl ethers or dialkyl ethers, diethylene glycol monoalkyl ethers or dialkyl ethers, triethylene glycol monoalkyl ethers or dialkyl ethers, propylene glycol monoalkyl ethers or dialkyl ethers, dipropylene glycol monoalkyl ethers or dialkyl ethers, and tripropylene glycol monoalkyl ethers or dialkyl ethers.
[0043] The amphiphilic alcohol represented by the above formula (3) is preferably a hydrophilic alkyl alcohol in which R3 in formula (3) has 4 to 7 carbon atoms, and examples thereof include at least one selected from the group consisting of 1-butanol (n-butyl alcohol, normal butanol), 2-methyl-1-propanol (isobutyl alcohol), 2-butanol (sec-butyl alcohol), 2-methyl-2-propanol (tert-butyl alcohol), all isomers of pentanol, all isomers of hexanol, 1-heptanol, 2-heptanol, 3-heptanol, and 4-heptanol.
[0044] The silica aerogel used in the solid composite constituting the heat insulating and sound insulating material of the present invention is preferably a hydrophobic aerogel having hydrophobic groups on the surface. Specifically, the particle surface is rendered hydrophobic by bonding with a tri-substituted silyl group represented by the following formula: 1 ,R 2 ,R 3 may be the same or different and are selected from alkyl groups having 1 to 18 carbon atoms or aryl groups having 6 to 18 carbon atoms, and are preferably a methyl group, an ethyl group, a cyclohexyl group, or a phenyl group. [ka]
[0045] The silica aerogel used in the solid composite has a porosity of 50% by volume or more, preferably 70% by volume or more, more preferably 80% by volume or more, and even more preferably 90% by volume or more.
[0046] The particle size of the silica aerogel is not particularly limited, but if the particle size is too small, the total particle gap ratio increases, and the ratio of nano-sized pores in the silica aerogel for sound insulation is low, which is not preferable. On the other hand, if the particle size is too large, the size of the particle gap increases, and air convection occurs between the large gaps, which may reduce the sound insulation effect, which is not preferable. A particle size range of 200 nm to 10 mm is preferable. Preferably, 90% or more of the silica aerogel is aerogel particles with a particle size within the range of 1 μm to 6 mm, more preferably within the range of 2 μm to 3 mm, and even more preferably within the range of 5 μm to 2 mm. If a silica aerogel with a particle size of 10 mm or more is used, the gap between the particles may become larger than the mean free path of air, which is not preferable. Furthermore, in order to reduce the gap between the particles, it is preferable that the bulk density of the silica aerogel powder has a small difference from the particle density. The closer the bulk density is to the particle density, the smaller the particle gap is, which is preferable. Furthermore, silica aerogel in which particles of various particle sizes are mixed is preferable rather than a single particle size.
[0047] As the silica aerogel having such a particle size, a commercially available product having the particle size within the range may be used, or silica aerogel having a particle size larger than the above range may be used after being appropriately pulverized.
[0048] Silica aerogel has a pore structure of several tens of nanometers that inhibits the mean free path of air, inhibiting the molecular motion of air and exhibiting high sound insulation. Because the particle surface has hydrophobic groups, water is prevented from seeping into or penetrating the pores even when dispersed in an aqueous medium. This means that the aerogel can maintain its inherent high porosity in the composition state and even after molding, and can therefore exhibit excellent sound insulation.
[0049] Silica aerogel, which has hydrophobic groups on its surface, cannot be uniformly dispersed in an aqueous medium by itself, but can be dispersed in an aqueous medium by the coexistence of a surfactant. However, when the content of the surfactant is low, the silica aerogel cannot be dispersed. On the other hand, when the concentration of the surfactant is increased to the extent that the silica aerogel can be dispersed, the dispersion medium easily penetrates into the pores. In the present invention, by using an organic nanofiber having an anionic functional group in combination with a surfactant, the dispersion medium does not penetrate into the pores of the silica aerogel, so that the porosity of the sound insulation material after molding can be highly maintained, and a composite material with high sound insulation properties can be obtained.
[0050] The aqueous dispersion containing the organic nanofibers and the silica aerogel particles for forming the solid composite contained in the thermal insulation sound insulation material of the present invention is prepared by mixing the above-mentioned components in a predetermined ratio.
[0051] In preparing an aqueous dispersion of silica aerogel particles, the order of mixing each component is not particularly limited. In view of the fact that the surface of silica aerogel is hydrophobic and that silica aerogel cannot be dispersed in water in the absence of a water-soluble nonionic surfactant, the following methods are available: (1) a method of mixing organic nanofibers having an anionic functional group, a water-soluble nonionic surfactant, and water, and then adding and mixing silica aerogel particles; and (2) a method of adding organic nanofibers having an anionic functional group to water, adding silica aerogel particles, and then adding and mixing the water-soluble nonionic surfactant. The addition and mixing can be either a method of adding a predetermined amount at once and mixing, or a method of adding and mixing little by little. In addition, if the viscosity of the dispersion of silica aerogel is high, after preparing the dispersion, a dispersion medium can be added to further dilute it.
[0052] The method of mixing for dispersing the silica aerogel particles in the dispersion medium is not particularly limited, and known methods such as shaking, stirring with a magnetic stirrer, mechanical stirring, vibration stirring, ultrasonic stirring, etc. However, if the shear force of the stirring is too strong, the pore structure of the silica aerogel may collapse, which is not preferable.
[0053] The stirring time is not particularly limited, but stirring is continued until a uniform dispersion is obtained. The temperature of the dispersion during stirring is not particularly limited, but the temperature may be appropriately adjusted depending on the application environment and application. If the temperature is too high, it is not preferable because there is a risk of decomposition or volatilization of the organic components. The temperature is preferably 15 to 150°C. More preferably, it is 20 to 120°C, and even more preferably, it is 23 to 90°C.
[0054] By dispersing hydrophobic silica aerogel particles in an aqueous dispersion medium containing organic nanofibers with anionic functional groups and a water-soluble nonionic surfactant, a creamy dispersion like a colloid in which the silica aerogel particles are dispersed as aggregates is obtained.
[0055] The shape and size of the aggregates (micelles) of silica aerogel particles that form the solid composite (the number of silica aerogel particles incorporated per micelle) depend on the content of organic nanofibers and surfactants, and the dispersion process and conditions. In particular, when the content of organic nanofibers is low, the aggregates of silica aerogel particles in the dried composite are polyhedral, such as hexagons. On the other hand, when the content of organic nanofibers is extremely high, the aggregates are spherical.
[0056] The concentration of the organic nanofibers having an anionic functional group in water is preferably 0.01 to 3% by weight, since within this range, the silica aerogel particles can be easily dispersed in the dispersion medium and the micelles of the dispersed silica aerogel particles can maintain high stability. If the dispersion medium is less than 0.01% by weight, the thixotropy or viscosity is too low, so that the micelles of the silica aerogel particles tend to coalesce and it is difficult to maintain stability, which is not preferable. On the other hand, if the dispersion medium is more than 3% by weight, the viscosity of the dispersion medium is too high, so that the silica aerogel particles cannot be dispersed well, and it is difficult to obtain a uniform dispersion liquid, which is not preferable. More preferably, the dispersion medium is 0.05 to 2.5% by weight, furthermore, 0.1 to 2.0% by weight, and even more preferably, 0.2 to 1.5% by weight.
[0057] The concentration of the water-soluble nonionic surfactant relative to the dispersion medium depends on the type of surfactant and is not particularly limited, but is preferably 0.2 to 20% by weight. More preferably, it is 2 to 15% by weight. If the concentration of the water-soluble nonionic surfactant is too low, it becomes difficult to uniformly disperse the silica aerogel in the dispersion medium. However, if the concentration of the water-soluble nonionic surfactant is too high, the dispersion medium not only wets the surface of the silica aerogel particles due to a decrease in surface tension, but also seeps or penetrates into the pores of the silica aerogel, so that the pores shrink due to evaporation of the solvent during drying, and the sound insulation property decreases.
[0058] The weight ratio of the organic nanofibers having anionic functional groups and the silica aerogel in the solid composite constituting the heat insulating sound insulation material of the present invention is not particularly limited, but if the weight ratio of the organic nanofibers having anionic functional groups is low, the dispersion of the silica aerogel becomes thermodynamically unstable, and there is a risk of phase separation occurring due to aggregation of the micelles of the silica aerogel particles during drying or molding. Furthermore, if the weight ratio of the organic nanofibers having anionic functional groups is too low, the composite becomes brittle after drying, which is not preferable. On the other hand, if the weight ratio of the organic nanofibers having anionic functional groups is too high, the performance derived from the silica aerogel decreases, which is not preferable. Therefore, the weight ratio of the silica aerogel particles and the organic nanofibers is preferably 95:5 to 60:40. More preferably, it is 90:10 to 70:30, and even more preferably, it is 85:15 to 75:25.
[0059] The solid composite is produced containing air therein. The air content varies depending on the blending ratio of the silica aerogel particles and the organic nanofibers, the concentration in the aqueous dispersion, etc., but typically 8 to 35 vol. % of air is present inside the solid composite.
[0060] In the heat insulating and sound insulating material of the present invention, the solid composite is formed inside the nonwoven fabric or open-cell foam. The sound insulating material of the present invention is composed of the solid composite, the inside of the nonwoven fabric or open-cell foam, and the space (air). Since the solid composite is larger than the mesh of the nonwoven fabric or the opening of the cell connection part of the open-cell foam, the solid composite does not fall off from the nonwoven fabric or the open-cell foam. In addition, since the silica aerogel particles form a solid composite with organic nanofibers (cellulose nanofibers), there is almost no powdering of the silica aerogel particles. FIG. 5 shows a micrograph of the heat insulating and sound insulating material obtained in Example 1 in which the solid composite is formed inside the glass wool, and FIG. 7 shows a schematic diagram of the sound insulating and sound insulating material in the case of the nonwoven fabric. The solid composite and the space (air) are formed in the space between the fibers of the nonwoven fabric, the solid composite is larger than the mesh of the glass fiber, and is present by adhering to the fibers of the nonwoven fabric.
[0061] The composition ratio of the solid composite in the thermal insulation sound insulation material of the present invention is preferably 5 vol% or more, more preferably 10 vol% or more, and further preferably 20 vol% or more, in terms of volume ratio, relative to the thermal insulation sound insulation material. Since the higher the composition ratio of the solid composite, the higher the sound insulation property, the thinner the thickness can be to obtain the same high sound insulation property.
[0062] The density of the heat and sound insulation material of the present invention depends on the material of the nonwoven fabric or open-cell foam and the ratio of silica aerogel to macropores. The density is not particularly limited, but from the viewpoint of light weight, 300 kg / m 3 It is preferable that: In this specification, the density of materials having internal voids, such as nonwoven fabrics, open-cell foams, solid composites, and thermal and acoustic insulation materials, is the apparent density.
[0063] If the thickness of the heat insulating sound insulation material of the present invention is too thin, the sound insulation effect is small, and if it is too thick, the advantage of space saving is lost. The thickness of the sheet is preferably 0.5 mm or more and 50 mm or less, and more preferably 1 mm or more and 10 mm or less.
[0064] Next, a method for producing the heat insulating sound insulation material of the present invention will be described. The thermal insulation soundproofing material of the present invention can be produced by impregnating a nonwoven fabric or an open-cell foam with an aqueous dispersion containing organic nanofibers and silica aerogel particles, or by immersing and impregnating a nonwoven fabric or an open-cell foam with an aqueous dispersion containing organic nanofibers and silica aerogel particles, and then drying the nonwoven fabric or the open-cell foam to form the solid composite in the internal space thereof.
[0065] When the aqueous dispersion containing organic nanofibers and silica aerogel particles has a high viscosity, it is preferable to degas the dispersion before impregnation because there is a high possibility that air bubbles are contained in the dispersion. The solid composite obtained from the degassed mixed aqueous dispersion is preferable because it has fewer voids larger than the mean free path of air, resulting in a composite with high sound insulation and strength.
[0066] Drying can be performed by any of the drying methods such as normal pressure drying, reduced pressure drying, or a combination of normal pressure and reduced pressure. Since the thermal conductivity of silica aerogel is low, it is also good to change to reduced pressure drying after some of the water or nonionic surfactant has evaporated during reduced pressure drying or normal pressure drying. The drying temperature and time depend on factors such as the boiling point of the surfactant, normal pressure or reduced pressure, etc. From the standpoint of productivity and application, it is preferable to use normal pressure drying and reduced pressure drying in combination.
[0067] The drying temperature and time are not particularly limited, but may be adjusted according to the boiling point of the surfactant and the shape of the mold. For example, 50 to 250°C is preferable. More preferably, it is 60 to 200°C, and further preferably, it is 75 to 180°C. If the temperature is too low, the drying time to remove the water and the surfactant becomes long, which is undesirable because of low productivity. On the other hand, if the drying temperature is too high, the water and the surfactant volatilize too vigorously, which may cause the formation of bubbles and defects, which is undesirable. In addition, if the drying temperature is too high, it is undesirable because the organic nanofibers decompose, or depending on the material of the nonwoven fabric or open-cell foam, there is a risk that the performance will decrease due to melting, or the shape will not be able to be maintained. Since the solid composite is formed in the internal space of the nonwoven fabric or open-cell foam, the heat insulating and sound insulating material will not crack when dried even if it is thick.
[0068] The composition ratio of the solid composite formed in the internal space of the nonwoven fabric or open-cell foam can be increased by increasing the concentration of the organic nanofibers and silica aerogel particles in the aqueous dispersion, but the composition ratio can also be increased by repeatedly impregnating the nonwoven fabric or open-cell foam with an aqueous dispersion containing the organic nanofibers and silica aerogel particles and drying it.
[0069] The heat insulating sound insulation material of the present invention exhibits different sound insulation performance depending on the type of nonwoven fabric or open-cell foam. That is, heat insulating sound insulation materials are classified into heat insulating sound insulation materials that exhibit almost the same sound insulation performance in the entire frequency range and heat insulating sound insulation materials that exhibit excellent sound insulation performance in the low and high ranges and frequency selectivity that transmits mid-range sounds. When glass wool or rock wool is used as the nonwoven fabric, those that exhibit almost the same sound insulation performance in the entire frequency range exhibit almost the same sound insulation performance in the entire frequency range, but when a nonwoven fabric other than glass wool or rock wool or an open-cell foam is used, they exhibit sound insulation performance that is excellent in sound insulation performance in the low and high ranges and frequency selectivity that transmits mid-range sounds.
[0070] When glass wool or rock wool is used, the heat insulating sound insulating material of the present invention has a normal incidence sound transmission loss in the frequency band of 200 Hz to 1000 Hz of 20 dB or more, preferably 30 dB or more, and more preferably 40 dB or less.
[0071] If the transmission loss is 20 dB, the sound volume will be reduced by 10%, if it is 30 dB, it will be about 3%, and if it is 40 dB, it will be 1%, so the noise will be reduced or almost eliminated.
[0072] The thermal insulating sound-insulating material of the present invention (hereinafter referred to as "frequency-selective thermal insulating sound-insulating material") using a nonwoven fabric or an open-cell foam other than glass wool or rock wool exhibits sound-insulating performance having excellent sound-insulating properties in the low and high frequency ranges and frequency selectivity that transmits mid-frequency range sounds, and its characteristics are as follows:
[0073] The frequency selective heat insulating sound insulating material is characterized in that the low frequency range is a frequency band of 400 Hz or less and the high frequency range is a frequency band of 1300 Hz or more, and that the frequency selective heat insulating sound insulating material has a minimum value of transmission loss in the mid frequency range between the low frequency range and the high frequency range.
[0074] The frequency selective heat-insulating sound-proofing material is characterized in that the average value of the transmission loss for each of the sound ranges is 6 dB or more in the low frequency range, 6 dB or more in the high frequency range, and 14 dB or less in the mid frequency range, and the minimum value of the transmission loss is 3 dB or less.
[0075] In addition, the frequency selective heat insulating sound insulation material can be characterized in a narrower range of the mid-range frequency band depending on the type of nonwoven fabric or open-cell foam, and there are frequency selective heat insulating sound insulation materials with a mid-range of 800 Hz to 1300 Hz and a mid-range of 400 to 1000 Hz. Examples of frequency selective heat insulating sound insulation materials with a mid-range of 800 Hz to 1300 Hz include cotton nonwoven fabric, melamine foam, carbon fiber nonwoven fabric, etc., and examples of frequency selective heat insulating sound insulation materials with a mid-range of 400 to 1000 Hz include 3M Thinsulate (registered trademark) nonwoven fabric, etc.
[0076] The average value of the transmission loss in each preferred frequency range of a frequency selective heat insulating sound insulating material having a mid-frequency range of 800 Hz to 1300 Hz is 6 dB or more, preferably 10 dB or more, and more preferably 20 dB or more in the low frequency range of 800 Hz or less; 6 dB or more, preferably 10 dB or more, and more preferably 20 dB or more in the high frequency range of 1300 Hz or more; and 8 dB or less, preferably 6 dB or less, and more preferably 4 dB or less in the mid-frequency range of 800 Hz to 1300 Hz; and the minimum value of the transmission loss is 3 dB or less, preferably 2 dB or less, and more preferably 1 dB or less. The frequency selective heat insulating soundproofing material having a midrange of 400 to 1000 Hz has an average value of transmission loss in each sound range of 6 dB or more, preferably 8 dB or more, and more preferably 10 dB or more in the low range of 400 Hz or less, and 6 dB or more, preferably 8 dB or more, and more preferably 10 dB or more in the high range of 1000 Hz or more, and 6 dB or less, preferably 3 dB or less, and more preferably 2 dB or less in the midrange of 400 to 1000 Hz, and the minimum value of transmission loss is 3 dB or less, preferably 2 dB or less, and more preferably 1 dB or less.
[0077] Ordinary sound-proofing materials follow a law known as the mass law, which states that the greater the mass per unit area (area density) and, for the same areal density, the higher the frequency (high-pitched sound range), the greater the transmission loss (sound-proofing performance). However, the thermal insulating sound-proofing material of the present invention has a large transmission loss despite its small areal density, and achieves high shielding performance even though it is light, ignoring the mass law.
[0078] The heat and sound insulating material of the present invention can be used as a device equipped with the material. The use of heat insulation soundproofing materials is to replace rubber-based soundproofing materials used in the engine room, interior and trunk of an automobile, thereby achieving significant weight reduction and reducing noise such as the aforementioned engine noise and noise radiated from tires. In addition to automobiles, it is also suitable for the bodies of transport vehicles such as railway cars, ships, airplanes and helicopters due to its light weight. It can also be used in factory blowers, presses, vacuum pumps, outdoor air conditioner units and boilers in stores and public facilities, and in the walls, floors and ceilings of houses. Examples of appliances equipped with heat and sound insulation materials include refrigerators, washing machines, vacuum cleaners, air conditioners, and speakers. Since the heat insulating soundproofing material of the present invention also has heat insulating properties, it is particularly suitable for electric vehicles, structures such as house walls, boilers and refrigerators from the viewpoint of energy saving. EXAMPLES
[0079] The present invention will be further described using examples. Note that the present invention is not limited to these examples. The manufacturing methods and property evaluation methods used in each example and each comparative example, the manufacturers of organic nanofibers having anionic functional groups, surfactants, and silica aerogel particles, and their preparation methods are shown below.
[0080] (Organic nanofibers) The organic nanofiber used was LeoCrysta (aqueous dispersion of 2% by weight of TEMPO-oxidized cellulose nanofiber) manufactured by Daiichi Kogyo Seiyaku Co., Ltd., a TEMPO-oxidized cellulose nanofiber in which some or all of the hydroxymethyl groups at the 6-position carbon on the surface of the cellulose nanofiber have been converted to carboxyl groups by TEMPO oxidation.
[0081] (Surfactant) Ethylene glycol monobutyl ether (EGMBE) manufactured by Nacalai Tesque, Inc. was used.
[0082] (Silica aerogel particles) The silica aerogel particles used were ENOVA AEROGEL MT1100 manufactured by Cabot Corporation. The particle size of MT1100 was 2 to 24 μm, and the particle density was 120 kg / m 3 It is.
[0083] (Nonwoven fabric) Glass fiber nonwoven fabric (glass wool) is 5mm or 10mm thick long fiber glass wool (density 105.1kg / m 3 , melting point / softening temperature 850℃) was used. As a cotton nonwoven fabric, absorbent cotton (Hakuju Cotton, manufactured by Hakujuji Co., Ltd., density 43.1 kg / m 3 ) was used. The carbon fiber nonwoven fabric was a 3 mm thick carbon felt (density 109.2 kg / m) made of carbon fiber made by baking and carbonizing acrylic fiber. 3 ) was used. As a microfiber nonwoven fabric, a 10 mm thick Thinsulate (manufactured by 3M, density 22.3 kg / m) consisting of polypropylene microfibers with a fiber diameter of 2 μm and polyester staple fibers with a fiber diameter of 25 μm was used. 3 ) was used. (Open-cell foam) Melamine foam with a thickness of 3 mm (density 82.5 kg / m) was used as the open-cell foam. 3 ) was used.
[0084] (Plate Glass) As plate glass, 5cm thick float glass (FL5, density 2500kg / m 3 ) was used.
[0085] (Transmission loss evaluation) The normal incidence sound transmission loss of the frequency selective heat insulating sound insulation material was measured using WinZac manufactured by Nihon Onkyo Engineering Co., Ltd., based on the transfer matrix method in accordance with ASTM-E2611. A sample of the frequency selective heat insulating sound insulation material cut into a disk shape with a diameter of 40 mm was placed in the device and measurements were taken in the frequency range of 200 to 5000 Hz. The environmental temperature was 25°C.
[0086] (Evaluation of density and areal density of frequency-selective thermal and acoustic insulation materials) A disk with a diameter of 41.5 mm is cut out with a certain area (S = 13.5 cm 2 The mass (W) of the frequency selective heat and sound insulation material was measured using a microelectronic balance and its thickness (d) was measured using a micrometer, and the density and areal density were calculated using the following formulas. Areal density is the weight per unit area. Density (kg / m 3 )=W(kg) / [d(m)×S(m 2 )] Areal density (kg / m 2 )=W(kg) / [S(m 2 )]
[0087] [Example 1] 13g of Rheocrysta water dispersion (solid content 2% by weight), 35g of distilled water, and 2.5g of ethylene glycol monobutyl ether were added to a 110ml screw-cap bottle and stirred with a stirrer until the Rheocrysta was uniformly dispersed, then 0.86g of silica aerogel (MT1100) was added, the lid was closed, and the bottle was shaken by hand for 3 minutes to obtain a cream-like dispersion. 34g of distilled water was added to the obtained dispersion and stirred with a stirrer to obtain a dispersion for impregnation. Glass wool of 10mm thickness and 6cm x 6cm was placed on a stainless steel tray, soaked in the dispersion for impregnation, and then dried in a dryer at 120°C for 3 hours to obtain a thermal insulation and sound insulation material. The thickness of the thermal insulation and sound insulation material after drying was 6mm. The density was 182kg / m 3 , surface density is 1.1kg / m 2 The thickness, density, surface density and normal incidence transmission loss of the obtained heat insulating sound insulation material were evaluated and the results are shown in Table 1, and graphs of normal incidence transmission loss against frequency are shown in Figures 1 and 3. An optical microscope photograph of the heat insulating sound insulation material is shown in Figure 5.
[0088] [Example 2] 13g of Rheocrysta water dispersion (solid content 2% by weight), 35g of distilled water, and 2.5g of ethylene glycol monobutyl ether were added to a 110ml screw-cap bottle and stirred with a stirrer until the Rheocrysta was uniformly dispersed, then 0.86g of silica aerogel (MT1100) was added, the lid was closed, and the bottle was shaken by hand for 3 minutes to obtain a cream-like dispersion. 13g of distilled water was added to the obtained dispersion and stirred with a stirrer to obtain a dispersion for impregnation. A 5mm thick, 6cm x 6cm glass wool was placed on a stainless steel tray, soaked in the dispersion, and then dried in a 120°C dryer for 3 hours to obtain a thermal insulation and sound insulation material. The thickness of the thermal insulation and sound insulation material after drying was 3.5mm. The density was 212kg / m 3 , surface density is 0.74kg / m 2 The thickness, density, surface density and normal incidence transmission loss of the obtained heat insulating sound insulation material were evaluated. The results are shown in Table 1, and the normal incidence transmission loss versus frequency graph is shown in Figure 3.
[0089] [Example 3] 13g of Rheocrysta water dispersion (solid content 2% by weight), 35g of distilled water, and 2.5g of ethylene glycol monobutyl ether were added to a 110ml screw-cap bottle, and stirred with a stirrer until the Rheocrysta was uniformly dispersed. Then, 0.86g of silica aerogel (MT1100) was added, the lid was closed, and the bottle was shaken by hand for 3 minutes to obtain a cream-like dispersion. A 5mm thick, 6cm x 6cm absorbent cotton was placed on a stainless steel tray, soaked in the dispersion, and dried in a 120℃ dryer for 3 hours to obtain a thermal insulation and sound insulation material. The thickness of the thermal insulation and sound insulation material after drying was 1mm. The density was 259kg / m 3 , surface density is 0.26 kg / m 2 The thickness, density, surface density and normal incidence transmission loss of the obtained heat insulating sound insulation material were evaluated. The results are shown in Table 2, and the normal incidence transmission loss versus frequency graph is shown in Figure 4.
[0090] [Example 4] 13g of Rheocrysta water dispersion (solid content 2% by weight), 35g of distilled water, and 2.5g of ethylene glycol monobutyl ether were added to a 110ml screw-cap bottle and stirred with a stirrer until the Rheocrysta was uniformly dispersed, then 0.86g of silica aerogel (MT1100) was added, the lid was closed, and the bottle was shaken by hand for 3 minutes to obtain a cream-like dispersion. 13g of distilled water was added to the obtained dispersion and stirred with a stirrer to obtain a dispersion for impregnation. A 3mm thick, 6cm x 6cm carbon felt was placed on a stainless steel tray, soaked in the dispersion, and then dried in a dryer at 120°C for 3 hours to obtain a thermal insulation and sound insulation material. The thickness of the thermal insulation and sound insulation material after drying was 2mm. The density was 184kg / m 3 , surface density is 0.37kg / m 2 The thickness, density, surface density and normal incidence transmission loss of the obtained heat insulating sound insulation material were evaluated. The results are shown in Table 2, and the normal incidence transmission loss versus frequency graph is shown in Figure 4.
[0091] [Example 5] 13g of Rheocrysta water dispersion (solid content 2% by weight), 35g of distilled water, and 2.5g of ethylene glycol monobutyl ether were added to a 110ml screw-cap bottle and stirred with a stirrer until the Rheocrysta was uniformly dispersed, then 0.86g of silica aerogel (MT1100) was added, the lid was closed, and the bottle was shaken by hand for 3 minutes to obtain a cream-like dispersion. 13g of distilled water was added to the obtained dispersion and stirred with a stirrer to obtain a dispersion for impregnation. A 10mm thick, 6cm x 6cm microfiber nonwoven fabric was placed on a stainless steel tray, soaked in the dispersion, and then dried in a dryer at 120°C for 3 hours to obtain a thermal insulation and sound insulation material. The thickness of the thermal insulation and sound insulation material after drying was 1.5mm. The density was 166kg / m 3 , surface density is 0.25kg / m 2 The thickness, density, surface density and normal incidence transmission loss of the obtained heat insulating sound insulation material were evaluated. The results are shown in Table 2, and the normal incidence transmission loss versus frequency graph is shown in Figure 4.
[0092] [Example 6] 13g of Rheocrysta water dispersion (solid content 2% by weight), 35g of distilled water, and 2.5g of ethylene glycol monobutyl ether were added to a 110ml screw-cap bottle and stirred with a stirrer until the Rheocrysta was uniformly dispersed, then 0.86g of silica aerogel (MT1100) was added, the lid was closed, and the bottle was shaken by hand for 3 minutes to obtain a cream-like dispersion. 13g of distilled water was added to the obtained dispersion and stirred with a stirrer to obtain a dispersion for impregnation. A melamine foam measuring 6cm x 6cm with a thickness of 3mm was placed on a stainless steel tray, soaked in the dispersion, and then dried in a dryer at 120°C for 3 hours to obtain a thermal insulation and sound insulation material. The thickness of the thermal insulation and sound insulation material after drying was 2.3mm. The density was 123kg / m 3 , surface density is 0.28kg / m 2 The thickness, density, surface density and normal incidence transmission loss of the obtained heat insulating sound insulation material were evaluated. The results are shown in Table 2, and the normal incidence transmission loss versus frequency graph is shown in Figure 4.
[0093] [Comparative Example 1] The thickness, density, surface density and normal incidence transmission loss of the 1 cm-thick long fiber glass wool used in Example 1 were evaluated. The results are shown in Table 1, and a graph of normal incidence transmission loss versus frequency is shown in FIG.
[0094] [Comparative Example 2] The thickness, density, surface density and normal incidence transmission loss of a 5 mm thick plate glass (FL5) were evaluated. The results are shown in Table 1, and a graph of normal incidence transmission loss against frequency is shown in Figure 2.
[0095] [Sound insulation of homogeneous materials] Generally, sound insulation, or transmission loss, follows the mass law, and it is said that the greater the mass (area density) of the material, the greater the sound insulation. According to the mass law, when a plane wave is assumed to be perpendicularly incident on an infinitely extending plate, the transmission loss is given by the following equation: TL0=20log 10 (f×m)-42.5 where TL0 is the transmission loss (dB), f is the frequency (Hz), and m is the surface density (kg / m 2 ).
[0096] [Calculation example 1] The surface density is the same as in the example, 1.1 kg / m 2 The sound insulation properties of the homogeneous material were calculated based on the above formula and the results are shown in Table 1, and the normal incidence transmission loss versus frequency graph is shown in Figure 2.
[0097] [Calculation example 2] The surface density is 12.5 kg / m, the same as the plate glass of Comparative Example 2. 2 The sound insulation properties of the homogeneous material were calculated based on the above formula and the results are shown in Table 1, and the normal incidence transmission loss versus frequency graph is shown in Figure 2.
[0098] The heat insulating sound insulating materials obtained in Examples 1 and 2, the comparative example, and the calculation example were evaluated for thickness, density, surface density, and normal incidence transmission loss. The results are shown in Table 1. [Table 1] As is clear from the results in Table 1, the heat and sound insulation material containing the silica aerogel particle / organic nanofiber solid composite obtained by impregnating glass wool in Example 1 has a surface density of 1.1 kg / m 2 Although it is small and lightweight, it has a large transmission loss in the 200Hz to 2000Hz range and has excellent sound insulation properties. 1 shows the normal incidence transmission loss versus frequency for the heat insulating sound insulation material of Example 1 and Comparative Example 1. The glass wool of Comparative Example 1, which is as light as Example 1, has almost no sound insulation. 2 shows the normal incidence transmission loss versus frequency for the heat insulating sound insulating material of Example 1, Comparative Example 2, and Calculation Examples 1 and 2. The transmission loss of Calculation Example 1 at 200 Hz to 2000 Hz calculated using the mass law with the surface density of Example 1 is considerably lower than that of Example 1. Furthermore, the plate glass of Comparative Example 2 and Calculation Example 2 show sound insulation equivalent to that of Example 1, but in order to obtain sound insulation equivalent to that of Example 1, a surface density of 12.5 kg / m is required. 2 As described above, the heat and sound insulation material of the present invention is a novel material that does not follow the mass law and overturns conventional wisdom. Figure 3 shows the normal incidence transmission loss versus frequency for the heat insulating sound insulation materials of Examples 1 and 2. In Example 2, the glass wool air is replaced with more solid composites than in Example 1, so that the same shielding performance can be obtained even with a thinner thickness, and the surface density is 0.74 kg / m 2 It has been possible to reduce this to as small as possible.
[0099] The heat insulating sound insulating materials obtained in Examples 3 to 6 were evaluated for thickness, density, surface density and normal incidence transmission loss. The results are shown in Table 2 and FIG. [Table 2] As shown in Table 2 and FIG. 4, when a nonwoven fabric or open-cell foam other than glass wool or rock wool is used, the thermal insulation sound-proofing material of the present invention exhibits excellent sound-proofing performance in the low and high frequency ranges and has frequency selectivity for transmitting mid-range sounds, and the frequency band of the mid-range sounds that are transmitted can be changed by changing the type of nonwoven fabric or open-cell foam to be impregnated. [Industrial Applicability]
[0100] The heat insulating sound insulation material of the present invention can block unpleasant low-frequency sounds below 250Hz that press on the ears, which cannot be achieved with conventional lightweight soundproofing materials (sound absorbing materials, sound insulation materials). Low-frequency sounds are generated not only from the muffled sound of automobile engines, but also from transportation equipment such as railway cars, ships, aircraft and helicopters, factory blowers, presses, vacuum pumps, outdoor air conditioners and boilers in stores and public facilities, etc., so it is expected to be used in a wide range of fields where light weight is particularly required. Since it can block sounds from 200Hz to 1000Hz, it can effectively block low-frequency road noise such as "goo", pattern noise such as "shaa" around 1000Hz, and engine transmission noise. Furthermore, its light weight is a great advantage not only for reducing the weight of transportation equipment such as automobiles, but also for the construction of buildings such as houses. In addition, since it also has heat insulating properties, it is effective in improving the comfort of living spaces such as houses and automobiles.
Claims
1. A thermal and sound insulating material having a basic structure in which an aggregate of silica aerogel particles is surrounded by a network of organic nanofibers having an anionic functional group, and a solid composite having a three-dimensional continuous structure in which a plurality of cells are closely spaced is formed inside a nonwoven fabric or an open-cell foam, and having a surface density of 0.26 kg / m 2 ~1.1kg / m 2 and a normal incidence sound transmission loss in the frequency band of 200 Hz or more and 315 Hz or less of 15.8 dB or more (however, this does not include the case where the heat insulating sound insulating material has a cured product of a heat insulating paint containing an acrylic resin and / or a urethane resin on at least a part of the surface and inside of the nonwoven fabric).
2. 2. The heat and sound insulating material according to claim 1, wherein the nonwoven fabric is made of at least one of natural fibers, inorganic fibers, regenerated cellulose fibers, semi-synthetic fibers, and synthetic fibers.
3. 2. The heat insulating soundproofing material according to claim 1, wherein the open-cell foam is at least one type of open-cell foam selected from the group consisting of urethane resin, melamine resin, vinyl acetate resin, polyvinyl chloride resin, acrylic resin, epoxy resin, silicone resin, olefin resin, latex, and rubber.
4. 2. The heat and sound insulating material according to claim 1, wherein the nonwoven fabric is made of glass wool or rock wool.
5. 2. The heat insulating sound insulation material according to claim 1, characterized in that the normal incidence sound transmission loss in a frequency band exceeding 315 Hz and not exceeding 2000 Hz is 20 dB or more.
6. A method for producing a thermal and sound insulating material, comprising the steps of: impregnating a nonwoven fabric or an open-cell foam with an aqueous dispersion containing organic nanofibers and silica aerogel particles (excluding cases where the aqueous dispersion contains an acrylic resin and / or a urethane resin) obtained by adding silica aerogel particles to an aqueous solution containing organic nanofibers having an anionic functional group and a water-soluble nonionic surfactant; and then drying the aqueous dispersion.
Citation Information
Patent Citations
High strength lightweight silica aerogel molded body and its production
JP1999139819A
High-performance thermal insulation materials
JP2013518961A
Fiber sheet
JP2014237910A
Segmented gel composite materials and rigid panels manufactured from these composite materials
JP2015524491A
Composite insulation containing inorganic aerogel and melamine foam
JP2016521670A